Study of Tuberculosis Related Topics in Baghdad, Iraq 2012-2016 Tuberculosis Related Topics (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective(s): The present study designed to explore topics related to Tuberculosis, such as new smearpositive cases, causes, treatment and new pulmonary positive cases in Baghdad City, Iraq for 2012-2016.Methods: A descriptive “retrospective” design was performed throughout the present study from the periodof November 12th 2017 to February 13th 2018. All registered tuberculosis patients in Baghdad, Iraq forthe period of 2012-2016. An instrument was constructed for the purpose of the study. Data were collectedfrom the health records at the National Tuberculosis Center, State TB center, and district TB center for theperiod of 2012 to 2016 with the use of the study instrument. Data were analyzed through the application ofdescriptive statistical data analysis approach of frequency, percent, incidence rate and ratio.Results: The study findings depicted that most of the new smear positive cases are accounted for theage group of (15-24) year old during the years of 2012-2016. Causes of Tuberculosis in the rural areawere accounted for poverty (39.95%), smoking (22.39%), untreated cases (12.4%), alcoholism (11.32%),malnutrition (10.30%) and overcrowded (3.57%) respectively, and accounted for alcoholism (27.77%),overcrowded (27.16%), malnutrition (24.69%), smoking (11.93%), poverty (7.62%) and untreated cases ofTuberculosis (0.80%) respectively in the urban area.Conclusion: The study concluded that Most of the new smear positive cases are accounted for the age groupof (15-24) year old during the years of 2012-2016. Patients, in 2014, had benefited out of the TuberculosisProgram more than others based on the success rate.